Manipulating item proportion and deception reveals crucial dissociation between behavioral, autonomic, and neural indices of concealed information. Issue 2 (3rd October 2014) - Suchotzki, Kristina; Verschuere, Bruno; Peth, Judith; Crombez, Geert; Gamer, Matthias
Abstract Developed as an alternative to traditional deception detection methods, the concealed information test (CIT) assesses recognition of critical (e.g., crime‐relevant) "probes." Most often, recognition has been measured as enhanced skin conductance responses (SCRs) to probes compared to irrelevant foils (CIT effect). More recently, also differentially enlarged reaction times (RTs) and increased neural activity in the bilateral inferior frontal gyrus, the right middle frontal gyrus, and the right temporo‐parietal junction have been observed. The aims of the current functional magnetic resonance imaging (fMRI) study were to (1) investigate the boundary conditions of the CIT effects in all three measures and thereby (2) gain more insight into the relative contribution of two mechanisms underlying enhanced responding to concealed information (i.e., orienting versus response inhibition). Therefore, we manipulated the proportion of probe versus irrelevant items, and whether suspects were instructed to actively deny recognition of probe knowledge (i.e., deceive) during the test. Results revealed that whereas overt deception was not necessary for the SCR CIT effect, it was crucial for the RT and the fMRI‐based CIT effects. The proportion manipulation enhanced the CIT effect in all three measures. The results indicate that different mental processes might underlie the response pattern in the CIT. While skin conductance responding to concealed information may best be explained by orienting theory, it seems that response inhibition drives RT and blood oxygen level dependent responding to concealed information. Hum Brain Mapp 36:427–439, 2015. © 2014 Wiley Periodicals, Inc.